Distal end of a ureteral double-J stent displaced into the contralateral ureter after percutaneous nephrolithotripsy: a case report - Chen, Junyong; Xie, Tao; Xu, Ya; Deng, Jian; Zhang, Jie; Zhu, Yumo; Li, Guiyuan (Frontiers in Medicine, 2023)
We report displacement of the distal end of a ureteral double-J stent into the contralateral ureter after percutaneous nephrolithotripsy (PCNL) in a 71-year-old man with a history of left kidney stones. Postoperative computed tomography imaging showed that the distal end of the left ureteral double-J stent was displaced into the right ureter, which resulted in persistent right renal colic when the nephrostomy tube was clipped and continuous urine leakage from the nephrostomy opening after the nephrostomy tube was removed. After the cystoscopic adjustment of the ureteral stent, the patient recovered uneventfully and was discharged home the next day.